Case Report of Atypical Juxtaglomerular Cell Tumor - Satoru Munakata; Eisuke Tomiyama; Hitoshi Takayama (Case Reports in Pathology, 2018)
Juxtaglomerular cell tumor (JGCT) is a rare renal tumor, producing renin and behaving almost in a benign fashion. So far, only three cases have been reported as malignant. We report a rare case with atypical JGCT. A 74-year-old male was referred to our hospital due to hypertension, proteinuria, and hematuria. Abdominal CT revealed a mass measured in 9.7×7.0 cm in the lower portion of the right kidney. Right kidney was removed laparoscopically. Grossly, white to tan tumor with massive hemorrhage and necrosis occupied the lower portion of the right kidney. Microscopically, tumor grew in a solid fashion. Tumor cells were polygonal to ovoid cells with round nuclei and clear to eosinophilic cytoplasm. Mitosis was found in 5 per 10 HPF. Immunohistochemically, tumor cells were stained by vimentin and CD34. Some tumor cells were also positive for renin. Electron micrograph showed near rhomboid crystalline structure in the tumor cells. Because of massive necrosis and mitotic figures, diagnosis of atypical (potentially malignant) JGCT was rendered. Gene mutations for IDH1, PIK3CA, K-ras, N-ras, Braf, and EGFR were not found by MBP-QP system.